2010
DOI: 10.1039/c001425g
|View full text |Cite
|
Sign up to set email alerts
|

NO2 quantum yields from ultraviolet photodissociation of methyl and isopropyl nitrate

Abstract: Quantum yields, Phi(NO(2)), are reported for the NO(2) formation channel (RO + NO(2)) following photodissociation of methyl and isopropyl nitrate (CH(3)ONO(2) and C(3)H(7)ONO(2)) at the tropospherically relevant wavelengths of 308-320 nm. Measurements were made using ultra-violet (UV) laser absorption and cavity ring down spectroscopy (CRDS) detection of the NO(2) photoproducts. Analysis of CRDS data to obtain NO(2) quantum yields required account to be taken of the spatially inhomogeneous NO(2) distribution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Figure 6 plots the transient absorption spectrum (averaged between t = 0.1 and t = 0.7 ms) of the photodissociation of isopropyl nitrate (C 3 H 7 ONO 2 ) at 266 nm. This reaction was recently shown to produce NO 2 with unity yield [13] at the experimental conditions used here (6.5 or 10 Torr, T = 300 K). Using the known initial concentration of isopropyl nitrate, its absorption cross-section at 266 nm, and the photolysis fluence, we expect to detect NO 2 products at concentrations of 2.23 -3.47•10 12 cm -3 .…”
Section: Effective Path Lengthmentioning
confidence: 99%
“…Figure 6 plots the transient absorption spectrum (averaged between t = 0.1 and t = 0.7 ms) of the photodissociation of isopropyl nitrate (C 3 H 7 ONO 2 ) at 266 nm. This reaction was recently shown to produce NO 2 with unity yield [13] at the experimental conditions used here (6.5 or 10 Torr, T = 300 K). Using the known initial concentration of isopropyl nitrate, its absorption cross-section at 266 nm, and the photolysis fluence, we expect to detect NO 2 products at concentrations of 2.23 -3.47•10 12 cm -3 .…”
Section: Effective Path Lengthmentioning
confidence: 99%
“…This is in agreement with the recent report for a NO 2 quantum yield of unity from photodissociation of methyl and isopropyl nitrate. [58] In the presence of O 2 , the H and HCO radicals formed from reactions 11 and 13b, will rapidly react with O 2 , resulting in the formation of HO 2 , H 2 O 2 and OH (reactions [16][17][18], and the oxidisation of NO 2 into HNO 3 (reaction 20) and HO 2 NO 2 (reaction 21). HC(O)O 2 was reported to be the intermediate product in the HCO þ O 2 reaction, and it can decompose rapidly to CO and HO 2 because of its instability (reactions 19).…”
Section: Reaction Mechanisms Based On Observed Products Photolysis Mementioning
confidence: 99%
“…It is also shown that there in minimal overlap with HONO and no overlap in the spectrum at all with PAN. It has been shown (Carbajo and Orr-Ewing, 2010;Talukdar et al, 1997) the UV-LEDs do not possess however. Both systems suffer some overlap with NO 3 radicals and BrONO 2 , more so in the case of PCL optics than for UV-LEDs.…”
Section: Possible Photolytic Interferences Of Blcsmentioning
confidence: 99%
“…non ozone) oxidants of NO. These perturbations have been used to infer the existence of oxidants such as peroxy radicals, or halogen oxides in the atmosphere (Bauguitte et al, 2012;Cantrell et al, 2003;Frey et al, 2015). The concentration of NO x varies from > 100 ppb (parts per billion) next to roads (Carslaw, 2005;Pandey et al, 2008) to low ppt (parts per trillion) in the remote atmosphere (Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation